A randomized controlled trial of the judicious use of safety behaviors during exposure therapy. (January 2019) - Blakey, Shannon M.; Abramowitz, Jonathan S.; Buchholz, Jennifer L.; Jessup, Sarah C.; Jacoby, Ryan J.; Reuman, Lillian; Pentel, Kimberly Z.
Abstract: Safety behaviors—actions performed to prevent, escape from, or reduce the severity of perceived threat—are typically eliminated during exposure therapy for clinical anxiety. Yet some experts have called for the strategic and "judicious use" of safety behaviors during exposure to improve treatment acceptability/tolerability without diminishing its efficacy. Empirical findings regarding this debate are mixed and existing work is subject to several methodological limitations. The current randomized controlled trial incorporated longitudinal design and multimethod assessment to compare the efficacy of traditional exposure with the elimination of safety behaviors (E/ESB) and exposure with judiciously used safety behaviors (E/JU). Adults with clinically significant spider fear ( N  = 60) were randomized to four twice-weekly sessions of E/ESB or E/JU. Self-report and behavioral measures were administered at pretreatment, posttreatment, and 1-month follow-up. Participants exhibited large effects on all measures from pretreatment to posttreatment, with no change from posttreatment to follow-up. There were no significant group differences in treatment outcome or treatment acceptability/tolerability. Exploratory analyses were used to compare behavioral and inhibitory learning processes between conditions. Clinical implications, study limitations, and future directions are discussed in terms of inhibitory learning theory. Highlights: Some patients refuse or relapse after exposure with elimination of safety behaviors (E/ESB). Exposure with judiciously used safety behaviors (E/JU) might facilitate exposure. Inhibitory learning (IL) suggests safety behaviors interfere with long-term outcome. E/ESB and E/JU were equally acceptable/tolerable and efficacious for spider phobia. E/JU facilitates behavioral approach but interferes with IL-related processes.